How to define a Systemically Important Financial Institution (SIFI): A new perspective - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
The recent financial crisis has demonstrated that a failure of Systemically Important Financial Institutions (SIFIs) could seriously damage the stability of the financial system. A precise and consistent definition of a SIFI is pivotal to ensure efficient and effective regulation of the global financial sector. This paper proposes a threefold test logic that allows to classify Financial Institutions as systemically important across the various industry segments.
urn:nbn:de:hebis:30:3-416169
Keywords: G10; G20; 330